Succulents : everything you need to select, pair, and care for succulents - Tuttle, Cassidy (Green thumb guides, 2022)
Succulents are plants that hold water in their leaves, such as cacti, aloe, and echeveria. They have captured the hearts of crafters, decorators, and plant lovers all over the world. Always popular as an outdoor plant in warm climates, succulents have found a new popularity as an indoor plant that's easy to care for and fun to look at. Includes: tips on successfully propagating new succulents from existing plants; extensive advice on choosing pots and unique planters, repotting succulents, and pairing varieties for maximum impact, and an index of succulents by colour and height that gives readers another tool for selecting the succulents that will look good.